Effect Of Rehabilitation On war causalities (lower amputation) Quality Of Life in Latakia - Gazal, Sawsan; ALkeer, Gafar (Latakia University Journal -Medical Sciences Series, 2018)
Disability affects the quality of life in general, and in various social, psychological, health and educational fields. The World Health Organization (WHO) defines quality of life as: the perception and perception of individuals of their status and location in life in the context of their culture and values ​​systems and their relationship to their goals, expectations, standards and considerations, a broad concept that is influenced by the physical health, psychological state, personal beliefs and social relationships, The outstanding features of its environment. [7] The quality of life of persons with disabilities is also linked to important variables such as their level of education, the sector of work they work in, their monthly income, and significant differences in the quality of life among persons with disabilities themselves, depending on the type of disability تؤثر الإعاقة الحركية سلباً على نوعية الحياة بشكل عام، وفي مختلف المجالات الاجتماعية والنفسية والصحية والتعليمية. وتعرّف منظمة الصحة العالمية (WHO) نوعية الحياة بأنها: إدراك وتصور الأفراد لوضعهم ومواقعهم في الحياة في سياق نظم الثقافة والقيم التي يعيشون فيها وعلاقة ذلك بأهدافهم وتوقعاتهم ومعاييرهم وباعتباراتهم، وهي مفهوم واسع النطاق يتأثر بالصحة الجسدية للشخص وحالته النفسية ومعتقداته الشخصية وعلاقاته الاجتماعية، وعلاقة ذلك بالسمات البارزة لبيئته. [7] كما ترتبط نوعية الحياة لدى الأشخاص ذوي الإعاقة، بمتغيرات هامة مثل مستواهم التعليمي، وقطاع العمل الذي يعملون فيه، ودخلهم الشهري، إضافة إلى وجود اختلافات هامة في نوعية الحياة بين الأشخاص ذوي الإعاقة أنفسهم تبعاً لنوع إعاقاتهم.[8]